Choosing between family-based and population-based association designs - Chung, Ren-Hua (Henry Stewart Talks, 2007)
Population-based association analysis, Population stratification, Genomic control, Structure analysis, Principal component analysis, Family-based association analysis, Parent-of-origin effect, Genome-wide association analysis, Combined test using family and population data
Archived at 2021/02/25